Partisipasi Masyarakat Terhadap Peningkatan Pembangunan Desa - Prastiwi Mardijani (Jurnal Paradigma, 2011)
In the preamble of the 1945 Constitution made clear that the Indonesian government in running the development process that covers the entire nation and the entire country of Indonesia. Then the responsibility of development is a responsibility of all walks of Indonesia. A development process was clear that an active government role in planned and implemented and sustained. Development in Indonesia covers all aspects of life, both in aspects of political, economic, social and cultural. Development will be successful if an activity that involves the participation of all communities within a country. Not only from the highest policy-making, planning, leadership, operational executor but also from the fishermen, laborers, farmers, small traders and others. So that development not only for the group or part of certain communities but to all citizens.